Osteoporotic Vertebral Fractures, Secondary Developing to Long Term Glucocorticoid and Cyclosyporin-A Use: A Case Report - Selda Çiftci; Jülide Öncü Alptekin; Zehra Duman; Cansu Mert; Rana Terlemez; Figen Yılmaz; Banu Kuran (Galenos Yayinevi, 2017)
Many side effects are encountered during the use of glucocorticoids. Osteoporosis is a common side effect of bone metabolism. The side effect increase with high dose and long-term use of steroids. In this article, we report a case of uncontrolled glucocorticoid use for 6 years due to ocular involvement due to Behçet's disease and a young male with osteoporotic fracture of the dorsal and lumbar vertebrae due to cyclosporine use for 3 years. To sum up, this case shows that steroids and combination treatments should be used with appropriate dose and duration in absolute indications and patients should be monitored in order.